A7.08 Novel agents for blocking the interaction of immune complexes with the activatory FCγRIIIA receptor. (24th February 2016) - Baxter, EW; Robinson, JI; Tomlinson, DC; Foster, RJ; Owen, RL; Win, SJ; Nettleship, JE; Tiede, C; Kankanala, J; Owens, RJ; Fishwick, CWG; McPherson, MJ; et al.
Abstract : Background and objectives: Protein-protein interactions are essential for the control of cellular functions and critical for regulation of the immune system. One example is the binding of Fc regions of Immunoglobulin G to their receptors (Fcγ Receptors). High sequence identity (98%) between the genes encoding FcγRIIIa and FcγRIIIb has led to the lack of specific agents against this important therapeutic target. We aimed to develop a novel drug development pipeline using artificial binding proteins called Adhirons both for the identification of novel therapeutics and to guide drug discovery through the identification of novel hot spots/ druggable surfaces on the receptor. Materials and methods: We cloned sequences encoding full-length FcγRIIa, FcγRIIIa and FcγRIIIb into expression vectors and created stably transfected HEK293 cells expressing each receptor. We also transiently transfected vectors encoding each ectodomain and the resulting proteins were purified. The FcγRIIIa ectodomain was used as a target for screening an Adhiron library using 'phage display. High affinity binders were used in cellular and biophysical assays (including Surface Plasmon Resonance (SPR) and X-ray crystallography). Results: Here we report the identification of FcγRIIIa-specific Adhirons. SPR experiments showed the selected Adhirons bind FcγRIIIa, but not FcγRIIa. We have demonstrated selective Adhiron blockade of IgG binding to FcγRIIIa, but not FcγRIIa or FcγRIIIb, by carrying out FACs assays in HEK293T cells ectopically expressing individual FcγRs. We also show blockade of effector functions downstream of FcγRIIIa signalling in THP-1-derived macrophage cells: these functions include immune complex-induced TNF release and phagocytosis. Co-crystal structures show one Adhiron binding directly to the Fc binding site whereas two others act as allosteric inhibitors. The structural basis for the specificity of the direct binder has been defined. Conclusions: The results suggest that Adhirons can be developed to inhibit protein-protein interactions that were previously considered to be "undruggable". Adhirons that inhibit the activatory FcγRIIIa (expressed on macrophages) but not FcγRIIIb (expressed on neutrophils), have been identified. This level of specificity has not been achieved using more conventional monoclonal antibody-based technology. Furthermore, the allosteric binders highlight a novel FcγRIIIa 'hot spot', which could be used in more conventional computational-based Medicinal Chemistry design tools. Topic: Novel Therapeutics